SQ-standardized house dust mite immunotherapy as an immunomodulatory treatment in patients with asthma - Blumberga, G (Blackwell Publishing Ltd, 2011)
BACKGROUND: Specific immunotherapy is the only treatment with the potential to prevent progression of the allergic disease and the potential to cure patients. The immunomodulatory ability of SQ-standardized house dust mite (HDM) subcutaneous immunotherapy (SCIT) was investigated in patients with allergic asthma. METHODS: Fifty-four adults with HDM-allergic asthma were randomized 1 : 1 to receive SQ-standardized HDM SCIT (ALK) or placebo for 3 years. At baseline, and after 1, 2 and 3 years of treatment, the lowest possible inhaled corticosteroid dose required to maintain asthma control was determined, followed by determinations of nonspecific and HDM-allergen-specific bronchial hyperresponsiveness, late asthmatic reaction (LAR), immediate and late-phase skin reactions, and immunological response. RESULTS: SQ-standardized HDM SCIT provided a statistically significantly higher HDM-allergen tolerance (P < 0.05 vs placebo) in terms of a 1.6-fold increase in PD(20) (HDM-allergen inhalation challenge), a 60-fold increase in skin test histamine equivalent HDM-allergen concentrations, reduced immediate- and reduced or abolished late-phase skin reactions, as well as fewer patients with LAR. PD(20) (methacholine inhalation challenge) increased initially and was similar between groups. House dust mite SCIT induced an initial increase in serum HDM-allergen-specific IgE (P = 0.028 vs placebo), which then declined to baseline value. House dust mite SCIT induced an increase in components blocking IgE binding to allergen [ΔIgE-blocking factor: 0.31; 95% CI of (0.26; 0.37)] after 1 year that remained constant after 2 and 3 years (P < 0.0001 vs placebo). CONCLUSION: SQ-standardized HDM SCIT induced a consistent immunomodulatory effect in adults with HDM-allergic asthma; the humoral immune response was changed and the HDM-allergen tolerance in lung and skin increased.